Removal of reactive dyes using micellar solubilization followed by coagulation and flocculation process / Adlina Aziz - Aziz, Adlina (2019)
Wastewater produced from dyeing process become an environmental threat to conserve biodiversity. Performance of conventional method for removing dyes like coagulation and flocculation is either high in cost operation or insufficient to meet effluent limits. Previous study discovered that a combination of membrane filtration with micellar solubilization such as micellar-enhanced ultrafiltration (MEUF) was quite efficient, however, the use of membrane was prone to cause fouling. Because of that, the aim of this research is to study the effectiveness of biodegradable plant-based surfactant, known as palm based esterquat (PBE) in removing Reactive Blue 4 (RB4) from synthetic wastewater via micellar solubilization followed by coagulation and flocculation process. The effect of PBE surfactant concentration and pH on RB4 removal efficiency were observed. In order to create an environmental-friendly and economical process, comparison between micellar solubilization and coagulation-flocculation process were discussed. Results from the studies revealed that RB4 was completely removed from synthetic wastewater at pH 4 via micellar solubilization followed by coagulation and flocculation with PBE surfactant concentration of 150 mg/L. Statistical analysis via multi linear regression shows that R2 and adjusted R2 for micellar solubilization were 0.968 and 0.886 whereas for coagulation and flocculation process were 0.902 and 0.412, respectively. Regression statistics and ANOVA verified that regression expression accounts for variability in the response variable.